FOREIGN INVESTED ENTERPRISES IN THE REPUBLIC OF UZBEKISTAN: MANAGEMENT TOOLS, MAIN FORMS, EVOLUTION AND TRENDS - Dr. Ubaydulla Nadirkhanov (European Science Publishing, 2024)
Since the launch of first economic reforms, attracting foreign investment has always been the focus of the government of the Republic of Uzbekistan. The article covers the evolution of foreign invested enterprises in 2015-2024. Particular attention is paid to the development of the joint venture (JV) and the wholly owned enterprise (WOFE) forms as a condition and a result of increased investment attractiveness of the country.
Keywords: foreign direct investment, foreign invested enterprises, joint ventures, knolly- foreign owned enterprises, management, business climate.